Participative Architecture: The Way to More Environmental Justice. (5th September 2018) - Hofmann, Susanne
Abstract : Do too many cooks spoil the broth? Not necessarily, if the metaphor is applied to architecture. As Berlin‐based practice Die Baupiloten has established, involving end users in design can have many benefits to both process and product – creative, qualitative, financial, social and practical. So what are the ingredients that make for a successful participatory design strategy? Die Baupiloten's founder and director Susanne Hofmann reveals the four‐stage approach that the firm has established, and describes how it has been applied in projects from schools to multigenerational communal housing.